Glutathione Peroxidase Activity, Plasma Total Antioxidant Capacity, and Urinary F2‐ Isoprostanes as Markers of Oxidative Stress in Anemic Dogs - Kendall, A. (J Vet Intern Med, 2017)
BACKGROUND: Oxidative stress plays a role in the pathophysiology of several diseases and has been documented as a contributor to disease in both the human and veterinary literature. One at‐risk cell is the erythrocyte, however, the role of oxidative stress in anemia in dogs has not been widely investigated. HYPOTHESIS/OBJECTIVE: Anemic dogs will have an alteration in the activity of glutathione peroxidase (GPx), a decrease in of total antioxidant capacity (TAC), and an increased concentration of urinary 15‐F(2)‐isoprostanes (F(2)‐IsoP) when compared to healthy dogs. ANIMALS: 40 client‐owned dogs with anemia (PCV <30%) age‐matched to 40 client‐owned healthy control dogs. METHODS: Prospective, cross‐sectional study. Whole blood GPx activity, plasma TAC, and urinary F(2)‐isoprostane concentrations were evaluated in each dog and compared between groups. RESULTS: Anemic dogs had significantly lower GPx activity (43.1 × 10(3) +/‐ 1.6 × 10(3) U/L) than did dogs in the control group (75.8 × 10(3) +/‐ 2.0 × 10(3) U/L; P < 0.0001). The GPx activity in dogs with hemolysis (10(3) +/‐ 0.8 × 10(3) U/L) was not significantly different (P = 0.57) than in dogs with nonhemolytic anemia (43.5 × 10(3) +/‐ 1.1 × 10(3) U/L). The TAC concentrations (P = 0.15) and urinary F(2)‐isoprostanes (P = 0.73) did not significantly differ between groups. CONCLUSIONS AND CLINICAL IMPORTANCE: Glutathione peroxidase activity was significantly decreased in anemic dogs indicating oxidative stress. Additional studies are warranted to determine if antioxidant supplementation would improve survival and overall outcome as part of a therapeutic regimen for anemic dogs.